MISKONSEPSI TUNJANGAN ASURANSI PUNGUTAN WAJIB DI INDONESIA DALAM PERSPEKTIF WELFARE STATE - Muhammad Cahya Dwiky Maulana; Khansa Alfiah; Sarah Mukhlisah; Kania Derlima Isnaeni; Akbar Nur Rohman; Khadijatun Nazmi; Arief Budiono (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The National Social Security System (SJSN) in Indonesia represents the implementation of the state's responsibility in realizing welfare as mandated by the 1945 Constitution of the Republic of Indonesia. However, the use of the term